If your name was changed at Ellis Island - Levine, Ellen; Parmenter, Wayne (New York : Scholastic Nonfiction, 2006)
Describes, in question and answer format, the great migration of immigrants to New York's Ellis Island, from the 1880s to 1914. Features quotes from children and adults who passed through the station.
G6
Keywords: Ellis Island Immigration Station (N.Y. and N.J.) -- History -- Juvenile literature; Ellis Island Immigration Station (N.Y. and N.J.) -- History; United States -- Emigration and immigration -- History -- Juvenile literature; United States -- Emigration and immigration -- History